PENGARUH KUALITAS PELAKSANAAN CORPORATE GOVERNANCE DAN INTELLECTUAL CAPITAL TERHADAP INTERNAL FRAUD PADA BANK UMUM INDONESIA - AHMAD HIKAM HIDAYATURRAHMAN (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
The purpose of this research is to discover the influence of the implementation quality of corporate governance and intellectual capital on the internal fraud. The implementation quality of corporate governance is measured by the scoring based on the self assesment rate of the good corporate governance implementation of the company. Moreover, the Value Added Intellectual Capital (VAIC) is used to measure the efficiency of the use of intellectual capital. While the internal fraud is measured by using the amount of deviations or fraud committed by the board of management, full-time employees and outsourced employees regarding to the process of bank operational activities that affect the financial condition of the bank significantly which is the impact of the deviation of more than Rp 100.000.000,00 (one hundred million rupiah). By using purposive samplingtechnique, 160 observation data were obtained out of 32 samples of commercial banks in Indonesia in the span of 5 years (2014-2018) which acquired from Indonesia Stock Exchange. The multiple regression analysis was used in this research to test the hypothesis. The results of this research show that (1) the implementation quality of the corporate governance has a negative and significant influences on the occurence of the internal fraud on the companies that exists in the samples; (2) the intellectual capital has a negative and significant influences on the occurence of the internal fraud on the commercial banks listed in Indonesia Stock Exchange.Keywords: Corporate Governance, Intellectual Capital, Internal Fraud, Commercial Bank of Indonesia, VAIC